The Post-thrombotic Syndrome-Prevention and Treatment: VAS-European Independent Foundation in Angiology/Vascular Medicine Position Paper - Cosmi, Benilde; Stanek, Agata; Kozak, Matja; Wennberg, Paul W.; Kolluri, Raghu; Righini, Marc; Poredos, Pavel; Lichtenberg, Michael; Catalano, Mariella; De Marchi, Sergio; Farkas, Katalin; Gresele, Paolo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Importance The post-thrombotic syndrome (PTS) is the most common long-term complication of deep vein thrombosis (DVT), occurring in up to 40–50% of cases. There are limited evidence-based approaches for PTS clinical management. Objective To provide an expert consensus for PTS diagnosis, prevention, and treatment. Evidence-Review MEDLINE, Cochrane Database review, and GOOGLE SCHOLAR were searched with the terms “post-thrombotic syndrome” and “post-phlebitic syndrome” used in titles and abstracts up to September 2020. Filters Were English, Controlled Clinical Trial / Systematic Review / Meta-Analysis / Guideline. The relevant literature regarding PTS diagnosis, prevention and treatment was reviewed and summarized by the evidence synthesis team. On the basis of this review, a panel of 15 practicing angiology/vascular medicine specialists assessed the appropriateness of several items regarding PTS management on a Likert-9 point scale, according to the RAND/UCLA method, with a two-round modified Delphi method. Findings The panelists rated the following as appropriate for diagnosis: 1-the Villalta scale; 2- pre-existing venous insufficiency evaluation; 3-assessment 3–6 months after diagnosis of iliofemoral or femoro-popliteal DVT, and afterwards periodically, according to a personalized schedule depending on the presence or absence of clinically relevant PTS. The items rated as appropriate for symptom relief and prevention were: 1- graduated compression stockings (GCS) or elastic bandages for symptomatic relief in acute DVT, either iliofemoral, popliteal or calf; 2-thigh-length GCS (30–40 mmHg at the ankle) after ilio-femoral DVT; 3- knee-length GCS (30–40 mmHg at the ankle) after popliteal DVT; 4-GCS for different length of times according to the severity of periodically assessed PTS; 5-catheter-directed thrombolysis, with or without mechanical thrombectomy, in patients with iliofemoral obstruction, severe symptoms, and low risk of bleeding. The items rated as appropriate for treatment were: 1- thigh-length GCS (30–40 mmHg at the ankle) after iliofemoral DVT; 2-compression therapy for ulcer treatment; 3- exercise training. The role of endovascular treatment (angioplasty and/or stenting) was rated as uncertain, but it could be considered for severe PTS only in case of stenosis or occlusion above the inguinal ligament, followed by oral anticoagulation. Conclusions and Relevance This position paper can help practicing clinicians in PTS management.